Evaluation of Humoral Response and Protective Efficacy of an Inactivated Vaccine Against Peste des Petits Ruminants Virus in Goats. Issue 5 (16th January 2015) - Cosseddu, G. M.; Polci, A.; Pinoni, C.; Capobianco Dondona, A.; Iapaolo, F.; Orsini, G.; Izzo, F.; Bortone, G.; Ronchi, F. G.; Di Ventura, M.; El Harrak, M.; Monaco, F.
Summary: Four goats were inoculated with an inactivated peste des petits ruminants virus (PPRV) vaccine. Three unvaccinated goats were kept as controls. After 36 days, the four goats were revaccinated. The immune response was monitored by virus neutralization test showing that two doses of the vaccine were able to stimulate strong immune response in all the vaccinated animals. The vaccinated goat and the controls were challenged with virulent PPRV intranasally. After PPRV challenge, the three control goats showed fever, viremia and virus excretion through mucosal surfaces, whereas the vaccinated goats were fully protected against PPRV infection and replication.